Through the looking-glass: on the other side of 'un'conclusive reflections. Issue 5 (2nd September 2016) - Hatten, Stephanie; McDonald, Denise
Abstract: This qualitative study explored the practices of a Technology Instructional Specialist (TIS) from the reflective vantage point of the specialist herself and multiple data sets collected from classroom teachers she mentored. The study examined the actions and impact of the TIS in assisting individual teachers with technology implementation through a reflective, circular process (i.e. action, reflection, modification, additional action). Data sources were comprised of: (1) survey on teachers' comfort levels for technology integration in an elementary classroom; (2) teacher interviews; (3) self and teacher reflective assessments of the TIS's mentoring; and (4) reflective journal notes of the TIS's experiences. Findings suggest that reflections on and development of differentiated technology mentoring processes and actions conducted within participating teachers' classrooms impacted their awareness of technology uses and pedagogical application. Most notably, reflections indicate that relational aspects of the TIS and teachers' interactions impacted the process of technology implementation in participating teachers' instructional practices. Practical suggestions for practitioners are provided.